1997
DOI: 10.1111/j.1365-2915.1997.tb00404.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hair density of beef cattle on Haematobia irritans horn fly populations

Abstract: We show the relationships that exist between the amount of hair and quantity of sebum on cattle skin and the population density of the horn fly, Haematobia irritans. Brahman and Chianina steers had means of 2390 and 1587 hairs per cm2, respectively, significantly more than the mean number of hairs on Angus, Brahman x Angus Crossbred, Charolais, and Red Poll steers. The Chianina steers had > 30% more sebum present on their skin and hair (0.58g/929 cm2) than the Angus, Charolais, and Red Poll steers at the Beef … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
0
18
1
1
Order By: Relevance
“…The zebu breed (Doube 1984, Steelman et al 1997) may explain the relatively low number of flies/cow observed in this study (maximum of 84). Low infestations have been found in other parts of the Brazilian mid-west, where zebu cattle have been raised extensively.…”
Section: Discussionmentioning
confidence: 82%
“…The zebu breed (Doube 1984, Steelman et al 1997) may explain the relatively low number of flies/cow observed in this study (maximum of 84). Low infestations have been found in other parts of the Brazilian mid-west, where zebu cattle have been raised extensively.…”
Section: Discussionmentioning
confidence: 82%
“…A desproporcional distribuição da mosca-doschifres em hospedeiros individualmente tem sido atribuída às características morfofisiológicas tais como, cor da pele (FRANKS; BURNS; ENGLAND, 1964), temperatura da pele (MORGAN, 1964), cor do pelo (PRUETT et al, 2003), densidade do pelo, e secreções sebáceas (STEELMAN et al, 1997). H. irritans ainda tem preferência por bovinos machos adultos (FARIA, 1998) e animais de sangue europeu (FARIA, 1998;CASTRO et al, 2008) ou mestiço (FARIA, 1998).…”
Section: Introductionunclassified
“…The more uniform horn ßy numbers on these cattle may reßect the uniform genetics, coat color, and coat density. Horn ßy numbers tend to decline as hair density increases (Steelman et al 1997) and may be less variable among cattle that have reduced hair density. Herds classiÞed into the moderate aggregation group included the small-frame Angus (Ͻ112.5 cm at the hips), Brahman, Charolais, LRC1, and LRC5 herds.…”
Section: Resultsmentioning
confidence: 97%
“…In a group of 23 breeding cows, the mean percentage of horn ßies on four ßy-resistant cows averaged Ͻ2% of the herd mean, whereas the mean percentage on Þve ßy-susceptible cows averaged Ͼ6% of the herd mean. The proportion of ßy-susceptible and ßy-resistant cattle in a herd can vary within and among breeds (Brown et al 1992, Steelman et al 1993) and may be inßuenced by factors such as size (Steelman et al 1996) and hair coat density (Steelman et al 1997). One consequence of this tendency for ßy populations to be aggregated within a herd is that estimates of horn ßy population density made by sampling within a herd may depart from the true mean if ßy-resistant or ßy-susceptible cattle are over-or underrepresented in the sample.…”
mentioning
confidence: 99%